Effects of the halo concentration distribution on strong-lensing optical depth and X-ray emission - Fedeli, Cosimo; Bartelmann, Matthias (Arxiv, 2017)
We use simulated merger trees of galaxy-cluster halos to study the effect of the halo concentration distribution on strong lensing and X-ray emission. Its log-normal shape typically found in simulations favors outliers with high concentration. Since, at fixed mass, more concentrated halos tend to be more efficient lenses, the scatter in the concentration increases the strong-lensing optical depth by $\lesssim50%$. Within cluster samples, mass and concentration have counteracting effects on strong lensing and X-ray emission because the concentration decreases for increasing mass. Selecting clusters by concentration thus has no effect on the lensing cross section. The most efficiently lensing and hottest clusters are typically the least concentrated in samples with a broad mass range. Among cluster samples with a narrow mass range, however, the most strongly lensing and X-ray brightest clusters are typically 10% to 25% more concentrated.